2018
DOI: 10.1186/s12978-017-0439-6
|View full text |Cite
|
Sign up to set email alerts
|

Muslim Women’s use of contraception in the United States

Abstract: Background: American Muslim women are an understudied population; thus, significant knowledge gaps exist related to their most basic health behaviors and indicators. Considering this, we examined American Muslim women's contraception utilization patterns. Methods: Self-reported data collected in late 2015 were analyzed. Women who identified as Muslim, were at least 18 years old, sexually active, and current residents of the United States (n = 224) met the inclusion criteria. Convenience sampling was employed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
160
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(176 citation statements)
references
References 42 publications
14
160
2
Order By: Relevance
“…Prior research indicates that examining Islam as a cultural paradigm is beneficial in that, this culture influences both health behaviors and health risks. 6 , 7 Considering the overarching goals of public health and medicine are to first, do no harm, and second, to improve overall population health, more thoughtful research on populations that are hard to reach due to being stigmatized, is urgently needed to better inform healthcare policy, clinical practice, and public health prevention efforts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research indicates that examining Islam as a cultural paradigm is beneficial in that, this culture influences both health behaviors and health risks. 6 , 7 Considering the overarching goals of public health and medicine are to first, do no harm, and second, to improve overall population health, more thoughtful research on populations that are hard to reach due to being stigmatized, is urgently needed to better inform healthcare policy, clinical practice, and public health prevention efforts.…”
Section: Resultsmentioning
confidence: 99%
“…1 , 4 , 5 Muslim Americans are an understudied population that is difficult to reach due to a range of factors that include this group's experiences with ongoing stigma and discrimination. 6 , 7 Regardless, it is still imperative that clinicians, policy makers, and public health practitioners understand and identify ways to improve this population's health and well-being, particularly considering the countervailing forces that could influence health behaviors. 6 , 7 Prior studies on Muslim Americans have focused on mental health, stigma, and sociopolitical measures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2000, there has been an increasing emphasis on humanizing the childbirth process, which occurs when women are provided care in a way that respects their rights as human beings and provides sufficient and adequate care throughout the whole birth process, involving them as active agents and capable of making decisions [ 9 11 ]. The need for respectful maternal care was recognized as an essential component of the recently updated recommendations for intrapartum care and safe childbirth by the World Health Organization [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of contraceptives and even contraception has been scantly publicized. A report suggested that Muslim women use of contraception is not significantly different from non-Muslim women in the United States [14] . However, that particular study stressed the need to further accurately identify factors and correlated pertaining to contraception and the use of OCPs among Muslim women.…”
Section: Introductionmentioning
confidence: 99%